Essentials of physical medicine and rehabilitation musculoskeletal disorders, pain, and rehabilitation - Frontera, Walter R. 1955-; Rizzo, Thomas D. 1959-; Silver, J. K. (Julie K.) 1965- (Philadelphia, PA Elsevier Saunders, 2015)
From sore shoulders to spinal cord injuries, Essentials of physical medicine and rehabilitation, third edition, provides you with the knowledge you need to get your patients moving again. This practical and authoritative new edition delivers easy access to the latest advances in the diagnosis and management of musculoskeletal disorders and other common conditions that require rehabilitation. Each topic is presented in a concise, focused, and well-illustrated format that features a description of the condition, a discussion of symptoms, examination findings, functional limitations, and diagnostic testing. An extensive treatment section covers initial therapies, rehabilitation interventions, procedures, and surgery.
Part 1 Musculoskeletal disorders -- Part 2 Pain -- Part 3 Rehabilitation
Includes bibliographical references and index
CHK-1011g Donated by CD Books International, Inc
Keywords: Musculoskeletal Diseases -- rehabilitation; Pain Management; Pain -- rehabilitation